Criterios para la selección y especificación de requisitos adicionales de materiales para sour service. - Malaisi, María Jimena Guadalupe (Instituto Sabato, 2007)
For over six decades there has been a continual need to develop new materials technology for use in petroleum operations involving exposure to H2S. Much of this effort has centred on the need for higher strength or more embrittlement resistant materials that can withstand increasingly aggressive service environments and higher levels of sulphur compounds and associated H2S. Relative to steels for oilfield service, activities have been generally directed at identifying grades of high strength casing and tubing that can withstand sour service conditions. Additionally, downstream petroleum refining and petrochemical equipment are being subjected to more aggressive service environments as a result of processing a greater variety of hydrocarbon feedstocks, some with increased levels of impurities. These impurities, such as H2S, organic sulphide compounds, and nitrogen compounds, result in high levels of H2S, cyanide and ammonia which can also produce conditions for cracking of steels used in plant pressure vessels and piping. Because of repetitive demand for certain items or special process specific requirements not completely covered by international standards, many companies have produced their own standards. There also may be certain situations companies have to deal with that are not covered at all by international standards. Special materials specifications, welding, and inspection procedures may be required to address process specific corrosion problems such as sulphide stress cracking or high temperature hydrogen attack. In many companies, international standards are sometimes modified to satisfy this need and to help the designer. This report has been developed to provide additional requirements for carbon steels used in wet H2S petroleum operations. It is based on international standards, users requirements and scientific research. It summarizes the results of laboratory tests and investigations of field and plant experience available from various sources in the published literature. Particular attention has been devoted to the environmental, metallurgical and fabrication parameters that play predominant roles in the various wet H2S cracking processes. It also attempts to provide and understanding of the basic hydrogen-related-cracking mechanisms in steel equipment.